Unusual thromboembolic complication during an anterior communicating artery aneurysm coiling. (17th February 2011) - Goyal, Sumit; Kumar, Subhash; Sharma, Rohitash; Husain, Shakir
Abstract : Thromboembolism during aneurysm coiling is a known complication with almost all thromboembolic phenomenon occurring ipsilateral to the side of vessel catheterization and sometimes bilaterally. A case is reported in which thromboembolism occurred exclusively on the opposite side of vessel catheterization, the first case to be reported, to our knowledge.